(untitled) (The Agriculturists, 2012)
Biofertilizer plays a significant role in crop cultivation with reduced the chemical fertilizer use. Three Trichoderma-enriched biofertilizers were evaluated in mustard and tomato cultivation at field condition. Sole application of biofertilizers didnt show remarkable contribution but all Trichodermaenriched biofertilizers when supplemented with N fertilizer significantly boosted up the growth and yield of mustard and tomato. Application of 50% N fertilizer along with 50% Trichoderma-enriched biofertilizers augmented 108 and 203% yields over control both in mustard and tomato, respectively which were 81.90 and 61.82% in mustard and tomato at standard doses of Nitrogen, Phosphorus and Potassium fertilizers. The present results suggest that Trichoderma-enriched biofertilizer could save at least 50% N fertilizer uses for mustard and tomato and could reduce excessive uses of NPK for crop cultivation. DOI: http://dx.doi.org/10.3329/agric.v10i2.13148 The Agriculturists 2012; 10(2) 109-119